The Application of Vicarious Liability Principle in Malpractice Cases by Health Workers in Indonesia - Nobel, Raden Muhammad; Westiartika, Dhira Taramadia; Abdulhamid, Muhammad; Prayuti, Yuyut (LEGAL BRIEF, 2025)
A party's liability for unlawful acts committed by another person under its responsibility is established by the principle of vicarious liability in civil law. This principle is crucial in determining the hospital's liability for malpractice committed by medical personnel under its supervision in the context of health services. This investigation employed a normative legal method that considered pertinent legal literature, doctrines, laws, and regulations. The results reveal that Article 1367 of the Civil Code normatively establishes a general basis for liability for the actions of others in a dependent relationship, whereas Article 46 of Law Number 44 of 2009 concerning Hospitals explicitly mandates that hospitals are accountable for the negligence of health workers employed in their institutions. Conversely, the practical implementation of this principle continues to encounter numerous impediments, including the absence of sufficient technical regulations, the challenge of substantiating formal employment relationships, and the absence of consistent jurisprudence. It is anticipated that the principle of vicarious liability will be enforced more effectively, which will enhance legal protection for patients, promote institutional accountability, and establish a health service system that is more transparent, fair, and prioritizes patient safety.